Dealing with anxiety and related disorders : understanding, coping, and prevention - Nydegger, Rudy V., 1943- (Santa Barbara, Calif. : Praeger, 2012)
"This thorough discussion and analysis of anxiety and related disorders looks at case studies, specific diagnostic categories, and treatments"--
"The book is about Dealing with Anxiety and Related Disorders - Understanding, Coping, and Prevention"--
What is anxiety? : The age of anxiety ; Diagnosing anxiety disorders ; Diagnostic and statistical manual ; Multiaxial diagnoses ; Mythes about anxiety ; People who suffer from anxiety disorders -- Living with anxiety disorders : [Case studies] -- The distribution and effects of anxiety disorders : costs, gender, age, and specific groups : Gender and anxiety disorders ; Age and anxiety ; Race, ethnicity, and anxiety disorders ; Homosexual groups and anxiety ; Religious groups and anxiety -- Theories of anxiety disorders : Biological theories ; Psychological theories ; Integrating the different theories ; Who is vulnerable? -- Physical responses and types of anxiety disorders I: generalized anxiety disorder and panic disorder -- Types of anxiety disorders II : phobias, posttraumatic stress disorder, and obsessive-compulsive disorder -- Treatments for anxiety disorders : Medical treatments for anxiety disorders ; Psychological treatments of anxiety disorders ; Other psychosocial treatment approaches -- Treatment methods for specific anxiety disorders and patient groups : Panic disorder ; Generalized anxiety disorder ; Social anxiety disorder ; Specific phobia ; Obsessive-compulsive disorder ; Posttraumatic stress disorder ; Other considerations in treating anxiety disorders -- Living with anxiety disorders : Who needs treatment? ; Where to seek treatment ; Types of mental health professionals ; Is treatment working, and when is it completed? ; What patients can do to help themselves: stress management -- Somatoform disorders : Malingering and factitious disorders ; Hypochondriasis ; Somatization disorder ; Conversion disorder ; Pain disorder ; Body dysmorphic disorder ; Other types of somatoform disorders -- Dissociative disorders : Background and history ; Dissociative disorders in general ; Depersonalization disorder ; Dissociative amnesia ; Dissociative fugue disorder ; Dissociative trance disorder ; Dissociative identity disorder ; Treatments of dissociative disorders -- Making sense of it all : Changing conceptions of anxiety and related disorders ; Coping with anxiety and related disorders ; Being a positive voice for good mental health ; Making a difference.
Includes bibliographical references and index.
Keywords: Anxiety disorders; Anxiety disorders -- Diagnosis; Anxiety disorders -- Treatment; Self-care, Health